Housing Health and Safety Decision Support System with Augmented Reality. (2015) - Kaklauskas, Arturas; Zavadskas, Edmundas Kazimieras; Cerkauskas, Justas; Ubarte, Ieva; Banaitis, Audrius; Krutinis, Mindaugas; Naimaviciene, Jurga
Abstract: Europe's residents spend more than 90% of their time in an enclosed environment. Hence generating conditions for a healthy lifestyle and bettering the quality of life in enclosed facilities take on special meaning because these can increase the work productivity of the residents, improve their quality of life, lower the rates of illnesses and save on expenses designated for medical treatments. The above-mentioned issues are related to a built environment's air pollution, the premise's microclimate, health and safety effects, climate change, real estate market value and the like. However, the Housing Health and Safety Decision Support System with Augmented Reality (HUSSAR) can analyse the above factors in an integrated way. The following models of HUSSAR are aimed to perform this function: Pollution Assessment and Recommender Model, Housing Health and Safety Analysis Model, Advisory Model, Augmented Reality Model and Healthy Homes Living Spaces Certification Model.